Associations of common variants at ALDH2 gene and the risk of stroke in patients with coronary artery diseases undergoing percutaneous coronary intervention. Issue 19 (May 2018) - You, Ling; Li, Chenze; Zhao, Jinzhao; Wang, Dao Wen; Cui, Wei
Abstract : Abstract: Limited data are available about the role of common variants at the aldehyde dehydrogenase 2 gene ( ALDH2 ) on the clinical outcome in Chinese patients with coronary heart disease (CHD) undergoing percutaneous coronary intervention (PCI). In the present study, a total of 1089 patients were consecutively enrolled from January 2012 and July 2013. Six common variants at ALDH2 gene, including rs2339840, rs4648328, rs4767939, rs11066028, rs16941669, and rs671, were selected to test the associations of those polymorphisms with the cardiovascular outcome in patients with CHD after PCI. The clinical endpoints included cardiovascular death, nonfatal myocardial infarction, and nonfatal stroke. The composite of clinical endpoints was defined as the primary endpoint, and every endpoint alone was considered as the secondary endpoints. The median follow-up time was 38.27 months. Our results showed that the common variant rs2339840 was independently associated with a lower risk of stroke in patients with CHD after PCI (codominant model, HR = 0.32, 95% CI, 0.11–0.91, P  = .074 for heterozygotes; HR = 0.25, 95% CI, 0.06–1.14, P =  .033 for homozygotes; dominant model, HR = 0.32, 95% CI, 0.14–0.74, P =  .007). However, no significant associations were found between other 5 single nucleotide polymorphisms (SNPs) and the clinical endpoints. For the first time, the common variant rs2339840 was reported to be a protective factor against stroke in CHD patients with PCI.